PENGARUH KUALITAS PRODUK DAN CITRA BANK TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS NASABAH (Studi pada Nasabah Tabungan BNI Taplus pada BNI Cabang Tembalang, Semarang) - Muhammad Fajar Utomo, 13.05.51.0189; Soliha, Euis (Students' Journal of Economic and Management, 2018)
This study aims to analyze the effect of product quality, bank image on satisfaction and its impact on customer loyalty of Bank BNI Taplus Tembalang Semarang Branch. The population in this study are customers who conduct transaction activities using BNI Taplus products at BNI Bank Tembalang Branch Semarang. The number of samples studied was as many as 100 people selected as respondents using purposive sampling technique. Data collection methods used in this study are questionnaires filled in by respondents. The analysis used in this study is multiple linear regression analysis to examine the partial effect of each independent variable, namely product quality and bank image on the dependent variable, namely customer satisfaction and loyalty. The results of this study indicate that product quality and bank image have a positive and significant effect on customer satisfaction, followed by product quality, bank image and satisfaction have a positive and significant effect on customer loyalty Bank BNI Taplus Tembalang Branch Semarang. Keywords: Product Quality, Bank Image, Customer Satisfaction and Loyalty.